P040 Monitoring defibrotide usage in paediatric patients undergoing HSCT with known risk factors for developing VOD/SOS. Issue 7 (19th June 2019) - Beirne, Michelle; Butler, Eileen; Fitzpatrick, Michael
Abstract : Aim: Defibrotide is licensed for the treatment of hepatic venous occlusive disease (VOD) following haematopoeitic stem cell transplant (HSCT). Up to April 2015 defibrotide was used as prophylaxis against VOD in our HSCT patients who were considered at high-risk for developing VOD. This practice was discontinued due to the lack of evidence of efficacy and increasing costs of the drug. The aims of this audit were to identify patients undergoing HSCT who had one or more risk factors for the development of VOD, to measure the incidence of VOD in this patient cohort after the discontinuation of prophylactic defibrotide and calculate the cost savings associated with the discontinuation of prophylaxis. Methods: All patients who underwent HSCT between Oct 2015 and Dec 2016 were included. Patient's medical records were reviewed and risk factors for VOD were identified. Risk factors for developing VOD post HSCT in our patient cohort were defined following a literature review of peer-reviewed papers identifying paediatric specific risk factors. 1 2 These were namely: patients aged ≤2 years, patients receiving a second transplant, conditioning with IV busulfan ± cyclophosphamide, and previous treatment with gemtuzumab ozogamicin. The theoretical dose of defibrotide for patients with known risk factors was calculated based on their weight at start of conditioning and the duration of treatment was based on the number of days conditioning the patient received plus 30 days following the date of transplant. The cost of a theoretical course of defibrotide for these patients was calculated to determine cost savings. Results: Of the 27 patients included in the study, 16 (59%) had one or more risk factors. The most common risk factor identified was conditioning with busulfan in patients ≤2 years of age (26% of patients). At present no patient post HSCT has developed VOD requiring treatment. One patient developed sub-clinical VOD which required no treatment and resolved spontaneously. Another patient received defibrotide as prophylaxis for VOD due to severe liver dysfunction prior to HSCT. There were substantial cost savings following the discontinuation of prophylactic defibrotide with a total of 2876 vials (180 vials/patient) saved during this time period. Conclusion: This audit validates our decision to discontinue use of prophylactic defibrotide and reserve its use for treatment of early VOD. References: Cheuk D, Wang P, Lee T, Chiang A, Ha S, Lau Y, Chan G. Risk factors and mortality predictors of hepatic veno-occlusive disease after pediatric hematopoietic stem cell transplantation. Bone Marrow Transplantation . 2007;40:935–944. Mohty M, Malard F, Abecassis M, Aerts E, Alaskar A, Alijurf M, NiChonghaile M. Sinusoidal obstruction syndrome/veno- occlusive disease: current situation and perspectives- a position statement from the European Society for Blood and Marrow Transplantation (EBMT). 2015; Bone Marrow Transplantation . 2015;50:781–789.